Double U Enterprise: portable vibratory tumbler / Nor Atira Latif Pudin, Muhamad Zuhdi Mohd Yusoff, Muhamad Firdaus Zulkafli, Muhamad Nor Haziq Hasmuni - Latif Pudin, Nor Atira; Mohd Yusoff, Muhamad Zuhdi; Zulkafli, Muhamad Firdaus; Hasmuni, Muhamad Nor Haziq (2017)
As for the business, we are providing a special device and machine for the Malaysian, As we go thru with the changes of environment, people nowadays are more likely to machines that can help them.